Taylor Myers: capstone - Myers, Taylor, artist (Colorado State University. Libraries, 2013)
The artist's statement: I am interested in the way functional objects enter our lives in everyday rituals and special happenings. I use comfortable accents and scale to speak to utilitarian use during daily rituals then embellish the pieces so they stand out during momentous occasions. In my life these balances of events (routines and celebrations) define my relation to objects. My most treasured memories come from parties and gatherings with close friends and family. I seek to create forms that speak to these occasions but that can conversely be enjoyed in everyday routine. My sources rely on the inspiration of sensuality and beauty. My intention is that the pieces generate intrigue long past the initial viewing. I look to specific historical examples to inform my work. I draw inspiration from Tudor and Elizabethan style fashion for the voluptuous shapes and rich textures. I then turn to the design of 1920's art deco style to inform my color pallet and surface decoration. I am attracted to art deco's use of rich colors and voluptuous shapes. This exaggeration is carried out the in forms of Elizabethan style dress with emphasis on rounded forms and billowy fabric. I am interested in these styles because of their exuberance and embellishment of human figure. I take the elements that best display to the viewer sensuality, voluptuousness, comfort, and beauty to create objects that have historical references without being overtly obvious. I utilize my favorite parts of history to create comfortable, functional objects. These pieces reflect my rituals and important gatherings that create distinctive meaning in my life.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.